2017
DOI: 10.1016/j.cej.2017.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Steam, dry, and steam-dry chemical looping reforming of diesel fuel in a 1 kW th unit

Abstract: Chemical looping reforming (CLR) is a process that enables the production of syngas/H 2 with CO 2 capture by using oxygen carriers that prevent direct contact between the fuel and air. This work presents the experimental results obtained in a 1 kW th CLR unit using a Ni-based oxygen carrier and diesel as fuel, as a first trial for further advancement with heavier liquid fuels. The influence of the main operating conditions, such as oxygen-to-diesel molar ratio and the H 2 O and/or CO 2 feed into the system, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In contrast, García-Labiano et al [123] and García-Díez et al [173,200] reported more than 100 hours of continuous operation in a 1 kW th continuous CLR unit using ethanol as fuel and two Ni-based oxygen carriers, NiO21-Al 2 O 3 and NiO18-Al 2 O 3. These authors experimentally demonstrated the viability of the CLR process with perfect control of the oxygen reacted in the fuel reactor for syngas production.…”
Section: Syngas/h 2 Productionmentioning
confidence: 96%
See 2 more Smart Citations
“…In contrast, García-Labiano et al [123] and García-Díez et al [173,200] reported more than 100 hours of continuous operation in a 1 kW th continuous CLR unit using ethanol as fuel and two Ni-based oxygen carriers, NiO21-Al 2 O 3 and NiO18-Al 2 O 3. These authors experimentally demonstrated the viability of the CLR process with perfect control of the oxygen reacted in the fuel reactor for syngas production.…”
Section: Syngas/h 2 Productionmentioning
confidence: 96%
“…The possibility for obtaining different H 2 /CO molar ratios under auto-thermal CLR conditions is particularly interesting, as these can be adjusted depending on the use of the syngas produced, as has been demonstrated with non-renewable fuels, e.g. synthetic fuels by the Fischer-Tropsch process [173].…”
Section: Production Of Syngas/h 2 From Biofuels By Chemical Looping Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Yus et al designed a two-zone fluidized-bed reactor and evaluated its performance on glycerol steam reforming using a Ni/Al 2 O 3 catalyst, and a H 2 yield of 1.3 mol-H 2 /mol-C and glycerol conversion of 93% were achieved. Nevertheless, sophisticated valving systems and low tolerance to particle volume changes during operation impede the further scaling up of these packed-bed or fluidized-bed platforms. , Nearly all CLR processes at a pilot-scale demonstration have adopted a configuration of two interconnected fluidized reactors. Garcia-Diez et al reported a CLR of diesel process using two interconnected fluidized-bed reactors, and they achieved a H 2 yield of 1.3 mol-H 2 /mol-C at a high solid circulation rate (8 kg/h) using Ni-αAl 2 O 3 . Garcia-Labiano et al demonstrated that interconnected fluidized-bed reactors were capable of reducing only 40–60% of Ni–Al 2 O 3 OCs at autothermal conditions (solid circulation rate: 3–9 kg/h).…”
Section: Introductionmentioning
confidence: 99%
“…The distinction of chemical looping processes from purely catalytic systems is that the chemical intermediate participates in each subreaction, though the net result is no change in the chemical state of the chemical intermediate. , Since each subreaction occurs in sequence instead of parallel, one can easily achieve product separation by controlling the location of the reactant feed and product outlet points in the reactor system. In the early 2000s, prompted by the awareness of global warming from carbon emission, chemical looping combustion (CLC) and chemical looping reforming (CLR) were used to convert fossil fuels to electricity and hydrogen, respectively. The specific application of the chemical looping concept of interest in the present manuscript is the use of metal oxides as the chemical intermediate, or oxygen carrier, to transport oxygen from air to the fossil fuel via redox reaction cycles. Such application has gained much popularity as the core concept for developing advanced processes for carbon capture and syngas generation applied to power and chemicals production applications, respectively .…”
Section: Introductionmentioning
confidence: 99%